Dissipative Kerr Solitons in a III‐V Microresonator. Issue 8 (22nd June 2020) - Moille, Gregory; Chang, Lin; Xie, Weiqiang; Rao, Ashutosh; Lu, Xiyuan; Davanço, Marcelo; Bowers, John E.; Srinivasan, Kartik
Abstract: Stable microresonator Kerr soliton frequency combs in a III‐V platform (AlGaAs on SiO2 ) are demonstrated through quenching of thermorefractive effects by cryogenic cooling to temperatures between 4 and 20 K. This cooling reduces the resonator's thermorefractive coefficient, whose room‐temperature value is an order of magnitude larger than that of other microcomb platforms like Si3 N4, SiO2, and AlN, by more than two orders of magnitude, and makes soliton states adiabatically accessible. Realizing such phase‐stable soliton operation is critical for applications that fully exploit the ultra‐high effective nonlinearity and high optical quality factors exhibited by this platform. Abstract : Dissipative Kerr soliton frequency combs in the AlGaAs‐on‐insulator platform are demonstrated, thanks to a cryogenic operation that suppresses thermorefractive effects that have been the limitation in reaching such phase stable states in this platform. The device requires only a few mW of pump power, enabled by the ultra‐high nonlinearity of the platform.